2015
DOI: 10.1016/j.bbmt.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of Dose-Escalated Busulfan Delivered by Prolonged Continuous Infusion in Allogeneic Transplant Patients

Abstract: Intensive chemotherapy or chemotherapy plus irradiation and allogeneic stem cell transplantation can be curative for patients with hematologic diseases. Reduced intensity transplants can also achieve cure, and result in less treatment related mortality but higher relapse rates. Thus, optimizing the conditioning regimens used in allogeneic transplantation remains an important goal. We conducted a Phase I/II trial to determine the maximum tolerated dose (MTD) and dose limiting toxicities (DLT) of a continuous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…† When the AUC is expressed in micromolar (micromoles/L) units, then the BU molecular weight (246.3 g/mol) must be used to calculate the AUC in mg/L units. BU dosing frequency has ranged from the traditional Q6H to Q24H [62,82] or as a continuous infusion [86]. For the first 20 years, BU was only available as 2-mg tablet that was administered Q6H.…”
Section: Faq7: What Is the Optimal Dosing Frequency Of Bu?mentioning
confidence: 99%
“…† When the AUC is expressed in micromolar (micromoles/L) units, then the BU molecular weight (246.3 g/mol) must be used to calculate the AUC in mg/L units. BU dosing frequency has ranged from the traditional Q6H to Q24H [62,82] or as a continuous infusion [86]. For the first 20 years, BU was only available as 2-mg tablet that was administered Q6H.…”
Section: Faq7: What Is the Optimal Dosing Frequency Of Bu?mentioning
confidence: 99%
“…Two trials implementing TITE-CCD were identified, and both were in an adult-only population. 11 , 12 One trial was a phase I trial, 12 and the other one was a phase I/II trial. 11 Both trials used TITE-CCD with a run-in period, that is, initial escalation was in cohorts of three patients until at least one patient developed a DLT.…”
Section: Resultsmentioning
confidence: 99%
“…However that was not feasible because of the lack of the necessary controlled studies and the published literature was too heterogeneous regarding patient population, conditioning regimen, Bu dosing, and Bu PK data [ 10 ]. Several studies provided recommendation of a maximally tolerated daily exposure of Bu of less than 6,000 mMxmin for 4 days [ 13 ], while others evaluated the maximally tolerated systemic exposure of intravenous Bu in combination with fludarabine and they showed that Bu can be safely escalated to an AUC of 7000 mMxmin or more without an appreciable difference in nonrelapse mortality [ 14 , 15 ] although with need of more patients and longer follow-up in those studies. In our patients, the median AUC targeted was 6000 uMolxMin and the median actual target given was 5354 uMolxMin.…”
Section: Discussionmentioning
confidence: 99%